Short-term (6 months) effects of tamoxifen on the contralateral breast parenchyma in patients who have undergone surgery for breast cancers: Significance of mammography in the radiologic evaluation of breast parenchyma - (:unkn) unknown (My University, 2003)
Objective: Our aim is to radiologically evaluate the effects of tamoxifen on the contralateral breast parenchyma in patients who have undergone surgery for breast cancer. Materials and Methods: We examined the mammograms of 121 women; 88 of them had breast cancer and 33 were healthy controls. The patients were grouped as follows; I: patients who received tamoxifen therapy after surgery, II: patients who did not take tamoxifen and III: healthy controls. The breast parenchyma area, the visualization of Cooper's ligaments and lactiferous ducts were evaluated in all 3 groups and analyzed statistically in order to determine the changes in breast density. Results: In patients who had undergone tamoxifen therapy, compared to non-tamoxifen patients, there was a prominent reduction in breast parenchyma (p<0.0001). This effect was more significant in premenopausal women (p<0.005). The effect of tamoxifen was most evident at the first 6th month follow-up. Conclusion: Tamoxifen reduces breast parenchyma and mammography is an objective method for demonstrating this reduction as a decrease in breast density.
Keywords: Breast carcinoma; Breast parenchyma; Mammography; Tamoxifen